IgG4-Related Tubulointerstitial Nephritis Pattern in 18F-FDG PET/CT. (October 2015) - Bélissant, Ophélie; Guernou, Mohamed; Rouvier, Philippe; Compain, Caroline; Bonardel, Gérald
Abstract : Abstract: A 17-year-old adolescent girl was admitted with chronic arthralgia, Raynaud phenomenon, pericarditis, and evidences of chronic diffuse inflammation. 18 F-FDG PET/CT scan was performed to search systemic vasculitis and showed diffuse moderate uptake in the kidneys. We suggested the existence of a nephritis, but the ultrasonography result was normal, and no treatment was introduced. Another 18 F-FDG PET/CT scan was performed 7 months later to explore abdominal pain. It showed again diffuse intense uptake in both kidneys. A proteinuria was highlighted, and renal biopsy allowed to diagnose IgG4-related disease.